Investigation of Internet User Behaviour in Indonesia - I Gusti Bagus Rai Utama; Dermawan Waruwu (Soshum: Jurnal Sosial dan Humaniora, 2019)
Research on the impact of the internet on educated users is done by an online survey that includes 126 respondents. Descriptive Statistical Analysis is used to explain the results of this study which are presented in tables, and qualitative discussions. Respondents are internet users. The survey results show that respondent who actually use the internet well have a positive impact on them, but on the contrary educated users who use the internet poorly can have a negative impact on them. Several beneficial effects for educated users are as a source of seeking knowledge, the internet as a medium of communication, it is used to exchange data, and it makes easy to business transaction in the trade sector. In other hand, the internet also has a negative impact if it is not used properly. These negative impacts include being addicted to adult content, being influenced by cruelty and sadism, engaging in deceptive acts, stealing credit card codes, engaging in online gambling and addiction, and even being affected for instant work. Cultivating ethical education when interact on the internet by religious message that will be able to keep themselves to use the internet for positive things. Promoting that internet for negative things can be legally punished by the law on information technology and electronic transaction